THE EFFECT OF PORTFOLIO ASSESSMENT AND LEARNING INDEPENDENCE ON LEARNING OUTCOMES BY CONTROLLING MATHEMATIC LOGICAL INTELLIGENCE - Gst Ayu Mahayukti; I Made Candiasa (Delta: Jurnal Ilmiah Pendidikan Matematika, 2022)
The purpose of the study was to examine the effect of portfolio assessment and learning independence on learning outcomes by considering logical mathematical intelligence (KLM). This experimental study uses a treatment by level 2×2 design. The population is all students of the Mathematics Study Program, FMIPA Undiksha who took the Integral Calculus course in the even semester of   2016 years, with a sample of 88 people taken randomly. Data were analyzed by ANACOVA. Based on the results of data analysis, it was found that the learning outcomes of students whose learning process was accompanied by a portfolio assessment were higher than students whose learning was accompanied by an essay assessment before and after KLM was controlled. The finding in this study is that learning independence has no significant effect on student learning outcomes before KLM is controlled, while after KLM is controlled learning independence has a significant effect on student learning outcomes.